(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines the harmful effects of noise on the environment and the human body, and analyzes the factors influencing the noise emission of traffic flow. The influence of road conditions, traffic composition, traffic speed, and road surface roughness on the noise level was studied. The noise levels of traffic flows on the central streets of Osh were studied, and measures to reduce their impact were recommended. The study was conducted to identify, reduce and prevent the impact of traffic noise on the environment and on the human body. The study used a comparative analysis method, which allows us to develop recommendations for reducing noise levels in the central streets of Osh. During the research, ways were proposed to resolve issues to improve the living comfort of the population, as well as reduce noise levels on the city’s road network.